EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DALAM PEMBELAJARAN PANCASILA TENTANG AKU BERPERILAKU PANCASILA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS II DI UPTD SD INPRES III KALABAHI TIMUR - Mardelisa Lanmai; Petrus Mau Tellu Dony; Imanuel Y. H Manapa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Effectiveness of the Numbered Heads Together (NHT) Cooperative Learning Model in Pancasila Learning About Me Behaving in Pancasila on the Learning Outcomes of Second Grade Students at the UPTD SD Inpres III Kalabahi Timur). This research is motivated by the low learning outcomes of second grade students in Pancasila education, due to teachers still using conventional learning models. The purpose of this study is to determine the effectiveness of the Numbered Heads Together (NHT) Cooperative Learning Model in Pancasila Education material in second grade students at the UPTD SD Inpres III Kalabahi Timur. This study used a pre-experimental quantitative research method with a one-group (pretest/posttest) approach, with a sample size of 24 students. The sampling technique used saturated sampling. Data collection was conducted using a one-group pretest/posttest design. Prior to the test, the material was tested for validity 84.28, reliability 0.8620, discriminatory power 0.8620, and test difficulty index 0.323. Furthermore, a prerequisite test for normality 0.323 was conducted. Hypothesis testing was conducted using a paired sample t-test. Data were analyzed using SPSS 22, yielding a t-test of 11.968 and a t-table of 1.714. This means that t-table > t-table, thus rejecting H0 and accepting H1. From these results, it can be concluded that using the Numbered Heads Together (NHT) Cooperative Learning Model for the topic of Recognizing the Pancasila Symbol, the Pancasila Principles and Symbols, the Meaning and Significance of Symbols, and the Application of Pancasila Values ​​at the UPTD SD Inpres III Kalabahi Kalabahi Timur can improve student learning outcomes.